Media Siber sebagai Sarana Komunikasi dalam Pelaksanaan Kehumasan Perguruan Tinggi Keagamaan - Alfiansyah Anwar; Ahmad Abbas (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
Cybermedia becomes a means of Islamic Universities to spur the public relations. One of them is IAIN Parepare which obtained first ranking for publication award concerning supervision from Ministry of Religion in 2019. This research seeks to demonstrate the existence of cyber media in leading the performance of public relations at IAIN Parepare. The type of this research is qualitative using nethnography approach. IAIN Parepare is object in this research. The result of this research demonstrates that the existence of cyber media spurs the implementation of performance of public relations of IAIN Parepare by utilizing main website of the campus, YouTube, Facebook, Twitter and Instagram so that information in terms of performance can be accessed by the public. Besides, IAIN Parepare conducts a contract cooperation with external cyber media in expanding the spread of campus information.